Effects of tai chi on subthreshold depression, stressors, resilience, burnout, negative emotion regulation and coping styles among chinese medical students in Yancheng city, China - Shiyue, Wang (2025)
Subthreshold depression represents specific depressive symptoms in individuals that fall short of meeting the diagnostic criteria for major depression and is highly prevalent among medical students facing heavy workloads and competitive pressures. This study examined the relationships among subthreshold depression, stressors, resilience, burnout, negative emotion regulation, and negative coping styles, and evaluated the effect of Tai Chi among Chinese medical students. The study also investigated the effect of Tai Chi intervention on subthreshold depression among students at Jiangsu Medicine College in Yancheng City through two study phases: a cross-sectional survey and a subsequent randomized controlled trial. In the phase 1,811 participants completed questionnaires, which were translated using forward and backward translation methods, and a structural equation model was used to examine the relationships between study variables. The Chinese version of the Center for Epidemiology Research Self-Rating Depression Scale (CES-D), Medical Student Stressor Questionnaire (MSSQ), Medical Professionals Resilience Scale (MeRS), Oldenburg Burnout Inventory (OLBI), Cognitive Emotion Regulation Questionnaire (CERQ), and Simple Coping Style Questionnaire (SCSQ) were used to measure subthreshold depression, stressors, resilience, burnout, emotion regulation, and coping styles among medical students. After establishing the validity and reliability of the questionnaires and determining the relationships between variables, the second phase of the study was conducted. The phase 2 assessed the effectiveness of Tai Chi intervention on subthreshold depression among medical students. A randomized controlled trial was conducted with 72 participants who were randomly assigned to either a 10-week Tai Chi program (three 40-minute sessions per week) or a no-intervention control group. Both groups completed questionnaires before and after the intervention. Data analysis was conducted using SPSS 29.0 and Mplus 8.3 software. Repeated measures analysis of variance (RM ANOVA) and repeated measures multivariate analysis of variance (RM MANOVA) were used to analyse the results of Phase 2. In the phase 1, the final structural model showed good fit with the data ( c2/df = 1.446, CFI = 0.984, TLI = 0.982, RMSEA = 0.023, SRMR = 0.030), revealing that stressors, burnout, negative emotion regulation, and negative coping styles were positively associated with subthreshold depression, whereas resilience was negatively associated. In the second phase, there were significant time and interaction effects for subthreshold depression, stressors, negative coping styles, and resilience (p < 0.001), burnout was significant in the interaction effect (p < 0.001), and negative emotion regulation was significant in the group effect (p < 0.001). In summary, this study: 1) confirmed the reliability and validity of the above scales among Chinese medical students; 2) revealed the relationships among subthreshold depression, stressors, resilience, burnout, negative emotion regulation, and negative coping styles; and 3) emphasised the positive effects of a 10-week Tai Chi course in reducing the level of subclinical depression among Chinese medical students